2019
DOI: 10.21203/rs.2.13561/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trauma to Transformation: The Lived Experience of Bereaved Parents of Children with Chronic Life-Threatening Illnesses in Singapore

Abstract: Background: In 2016, over 6.6 million children died globally, and 245 children died in Singapore. Chronic illnesses are prevalent causes of child mortality around the world. Despite growing research that examines the lived experience of parents bereaved by their child’s chronic life-threatening illness, there is no such study within the Asian context. Methods: To bridge this knowledge gap, meaning-oriented, strength-focused interviews were conducted with 25 parental units (i.e. 6 couples, 13 lone mothers, 4 l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…Interestingly, the findings of Ow 11 differed from the recent Singapore studies, 12,13 that reported parents of children with various chronic illnesses focused on the practical aspects of coping at the early stage of receiving their child’s diagnosis. Emotional needs, however, were more likely to surface after children had died from their illness.…”
Section: Introductioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, the findings of Ow 11 differed from the recent Singapore studies, 12,13 that reported parents of children with various chronic illnesses focused on the practical aspects of coping at the early stage of receiving their child’s diagnosis. Emotional needs, however, were more likely to surface after children had died from their illness.…”
Section: Introductioncontrasting
confidence: 86%
“…Emotional needs, however, were more likely to surface after children had died from their illness. Nevertheless, those recent studies 12,13 were based on the retrospective experiences of bereaved parents whose children had died from a number of chronic illnesses including cardiac and renal conditions, cerebral palsy, cerebral vein thrombosis and childhood cancer. Moreover, as the loss of a child can result in significant changes in parents’ perception of life experiences 14 (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…85,99,113 In addition, there has been little-no focus on young parents (aged between 13–25 years). A wealth of research has examined the experiences of middle aged parents; five studies included parents aged over 20 years 10,72,80,88,104 and six gave an account of parents over 65, 9,58,60,73,74,110 however their gender and number in that specific age range has not been specified. In 27 studies (44%) parents’ age was not specified at all.…”
Section: Discussionmentioning
confidence: 99%
“…6,73,77,89,94,97,105 Through the hardship they learnt what was valuable for them. 8,23,27,60,71,77,90–93,95 Some focused on hope and defiance to move forward in life, 6,23,27,28,77,88,102 whereas others talked about the importance of acceptance. 1,8,27,28,57,59,73,91,94,105,106 Religion was also a way to cope and manage the difficulty of the experience.…”
Section: The Fall Of the Curtain: An Irrevocably Altered Worldmentioning
confidence: 99%